Pengaruh pemberian kompres hangat jahe untuk mengurangi nyeri sendi pada lansia di Gampong Neusu Aceh, Kecamatan Baiturrahman, Kota Banda Aceh (The effect of warm ginger compresses to reduce joint pain in the elderly in Neusu Aceh Village, Baiturrahman District, Banda Aceh City) - Mulyadi, Nabila; Febriana, Dara; Yanti, Sarini Vivi (Buletin Pengabdian, 2023)
Pain in joint movement can be caused by various causes, one of them is associated with increasing age. Joint pain in the elderly is considered to be the result of various pathological processes, one of which can cause pain in the elderly is disturbances that occur in the joint cartilage matrix. In general, this joint pain makes sufferers feel uncomfortable when the joints are touched, swelling, inflammation, stiffness and limited movement are seen. The purpose of this activity is to report the results of nursing care for the elderly with joint pain in Neusu Aceh Village, Baiturrahman District, Banda Aceh City. The nursing diagnosis that appears in this case is chronic pain. The implementation provided includes non-pharmacological pain management using red ginger warm compresses to reduce the pain scale in client. Based on the evaluation of the implementation that has been carried out to client, there was an increase in knowledge about ginger warm compress therapy for joint pain, a decrease in the pain scale from 5 numerical rating scale (NRS) to 3 NRS, and pain in both knees was reduced. It is suggested to the village head and elderly health cadres in Neusu Aceh Village to increase the knowledge of the elderly regarding joint pain through the elderly Posyandu activities.